Increased risks of cardiovascular diseases and insulin resistance among the Orang Asli in Peninsular Malaysia. (December 2016) - Tuan Abdul Aziz, Tuan; Teh, Lay; Md Idris, Muhd; Bannur, Zakaria; Ashari, Lydiatul; Ismail, Adzrool; Ahmad, Aminuddin; Isa, Kamarudzaman; Nor, Fadzilah; Rahman, Thuhairah; Shaari, Syahrul; Jan Mohamed, Hamid; et al.
Abstract Background Despite the strategic development plan by the authorities for the Orang Asli, there are six subtribes of which their population numbers are small (less than 700). These minorities were not included in most of the health related studies published thus far. A comprehensive physiological and biomedical updates on these small subtribes in comparison to the larger subtribes and the urban Malay population is timely and important to help provide appropriate measures to prevent further reduction in the numbers of the Orang Asli. Methods A total of 191 Orang Asli from different villages in Peninsular Malaysia and 115 healthy urban Malays were recruited. Medical examinations and biochemical analyses were conducted. Framingham risk scores were determined. Data was analyzed using IBM SPSS Statistics, Version 20.0. Results A higher percentage of the Orang Asli showed high insulin levels and hsCRP compared to the healthy Malays denoting possible risk of insulin resistance. High incidences of low HDL-c levels were observed in all the Orang Asli from the six subtribes but none was detected among the urban Malays. A higher percentage of inlanders (21.1 % of the males and 4.2 % of the females) were categorized to have high Framingham Risk Score. Conclusions Orang Asli staying both in the inlands and peripheries are predisposed to cardiovascular diseases and insulin resistance diabetes mellitus. The perception of Orang Asli being healthier than the urban people no longer holds. We believed that this information is important to the relevant parties in strategizing a healthier community of the Orang Asli to avoid the vanishing of the vulnerable group(s).